A queer history of fashion : from the closet to the catwalk - Steele, Valerie; Breward, Christopher; Cole, Shaun (New Haven New York : Yale University Press Fashion Institute of Technology (FIT), 2013)
Fonds Suzan Daniel (FSD)
Engels
Monografie